Management of narrow stalked giant omphalocele using tissue expansion, staged closure, and amnion preservation technique - Zach Z. Zhang; Candace Haddock; Cynthia Verchere; Jugpal S. Arneja; Erik D. Skarsgard (Elsevier, 2019)
Giant omphaloceles (GO) frequently present challenges to closure that are often influenced by patient factors, including degree of visceroabdominal disproportion, associated comorbidities (including pulmonary hypoplasia), and variation in surgeon preference for both technique and timing of abdominal wall reconstruction.In this case report, we describe our experience with a GO that presented the unique challenge of an uncharacteristically small fascial defect through which all structures (including liver) were herniated. The challenges of the small defect, both in potentially limiting the growth of healthy neoskin and preventing any degree of visceral reduction by compression are highlighted. An innovative reconstructive solution developed in collaboration with plastic surgery is described. Keywords: Giant omphalocele, Tissue expander, Amnion preservation